Improved humid air condensation heat transfer through promoting condensate drainage on vertically stripe patterned bi-philic surfaces. (October 2020) - Lee, Junbeom; Lee, Seunghwan; Lee, Jaeseon
Highlights: Wenzel state droplets on the hydrophobic surface are not quickly discharged into the condensate. Bi-philic stripe pattern surfaces were fabricated to enhance condensate recovery. Condensate recovery was increased by 15% compared to the homogeneous super-hydrophilic surface. A bi-philic surface condensate discharge model determined the optimal stripe pattern. Abstract: Even when dropwise condensation occurs on the super-hydrophobic surface, the condensed water droplets stick to the surface in the Wenzel state, resulting in lower drainage rate than the super-hydrophilic surface. Condensate that is not drained consequently degrades condensation heat transfer performance over time. In this study, it was considered that the striped patterned bi-philic surface could improve the condensation heat transfer in that droplet of the near super-hydrophobic area can be quickly removed and drained to a nearby super-hydrophilic region. Rapid drainage of condensate from the near super-hydrophobic surface can result in the renewal of new dropwise condensation, which can lead to increased heat transfer. Condensate discharges from bi-philic surfaces fabricated by material printing were measured and compared to condensate discharges from fully super-hydrophilic and near super-hydrophobic surfaces. As decreasing the stripe width of the bi-philic surface, the drainage rate is improved due to the rapid growth of the droplet nucleate on the near super-hydrophobic surface and the increment of the drainage path. The maximum condensate discharge from the bi-philic surface was measured to be 15% higher than that of the entirely super-hydrophilic surface. The amount of condensate recovery from the bi-philic surface was predicted through film and dropwise condensation combined modeling. Through this model, the amount of condensate recovered from the bi-philic surface was predicted within the 8% error range. Determination of the optimal stripe pattern to maximize the amount of condensate recovery can be made through developed modeling. The optimized stripe design of bi-philic surface resulted in a 25% increase in condensate discharge compared to the entirely super-hydrophilic surface.